FAKTOR-FAKTOR YANG MEMPENGARUHI PERUBAHAN VOLUME USAHA DAN PENDAPATAN PENGUSAHA KULINER DI KOTA DENPASAR - Mahendra, Wayan Putra; Ayuningsasi, Anak Agung Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.02.TAHUN.2023, 2023)
This study aims 1) to analyze the effect of capital, the number of customers and working hours on changes in the business volume of culinary entrepreneurs in Denpasar City, 2) to analyze the effect of capital, the number of customers, working hours, and changes in business volume on the income of culinary entrepreneurs in Denpasar City, and 3) to analyze changes in business volume in mediating the effect of capital, number of customers, and working hours on the income of culinary entrepreneurs in Denpasar City. The research population is culinary entrepreneurs in Denpasar City. The sampling technique used is nonprobability sampling with a quota sampling approach or determined based on the allotment. The number of samples in this study was 100 samples as respondents were taken evenly in each sub-district in Denpasar City by using accidental sampling. The analysis technique used is path analysis. The results showed that capital, number of customers, and working hours had a positive and significant effect on changes in the business volume of culinary entrepreneurs in Denpasar City. Capital, number of customers, working hours, and changes in business volume have a positive and significant impact on the income of culinary entrepreneurs in Denpasar City. Changes in the business volume are variables that significantly mediate the effect of capital, number of customers, and working hours on the income of culinary entrepreneurs in Denpasar City